At last comes love - Balogh, Mary (Dell historical romance., 2009)
A scandal sends Duncan Pennethorne back home where he finds out he must wed in fifteen days or be cut off without a penny. He learns that Margaret Huxtable is looking for a husband so he sets off to convince her to accept his marriage proposal.